ChemInform Abstract: Aqueous Morita—Baylis—Hillman Reaction of Unprotected Isatins with Cyclic Enones. Issue 14 (8th April 2014) - Gomes, Juliana; Sirvent, Jordi; Moyano, Albert; Rodrigues, Manoel T. Jr.; Coelho, Fernando
Abstract Readily available 6, 7‐dihydro‐5H‐pyrrolo[1, 2‐a]imidazol‐7‐ol is used as an unique catalyst for the aqueous Morita—Baylis—Hillman (MBH) reaction between unprotected isatins and cyclic enones.